Novel bicyclo[3.1.0]hexane analogs as antagonists of metabotropic glutamate 2/3 receptors for the treatment of depression. Issue 23 (1st December 2016) - Dressman, Bruce A.; Tromiczak, Eric G.; Chappell, Mark D.; Tripp, Allie E.; Quimby, Steven J.; Vetman, Tatiana; Fivush, Adam M.; Matt, James; Jaramillo, Carlos; Li, Renhua; Khilevich, Albert; Blanco, Maria-Jesus; et al.
Graphical abstract: Abstract: Negative modulators of metabotropic glutamate 2 & 3 receptors demonstrate antidepressant-like activity in animal models and hold promise as novel therapeutic agents for the treatment of major depressive disorder. Herein we describe our efforts to prepare and optimize a series of conformationally constrained 3, 4-disubstituted bicyclo[3.1.0]hexane glutamic acid analogs as orthosteric (glutamate site) mGlu2/3 receptor antagonists. This work led to the discovery of a highly potent and efficacious tool compound18 (hmGlu2 IC50 46 ± 14.2 nM, hmGlu3 IC50  = 46.1 ± 36.2 nM). Compound18 showed activity in the mouse forced swim test with a minimal effective dose (MED) of 1 mg/kg ip. While in rat EEG studies it exhibited wake promoting effects at 3 and 10 mg/kg ip without any significant effects on locomotor activity. Compound18 thus represents a novel tool molecule for studying the impact of blocking mGlu2/3 receptors both in vitro and in vivo .